Community-Based Health Insurance Enrollment and Child Health Service Utilization in Northwest Ethiopia: A Cross-Sectional Case Comparison Study - Atnafu A; Gebremedhin T (Dove Medical Press, 2020)
Asmamaw Atnafu, Tsegaye Gebremedhin Department of Health Systems and Policy, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Asmamaw AtnafuDepartment of Health Systems and Policy, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, PO Box: 196, Gondar, EthiopiaEmail asme2002@gmail.comPurpose: Utilization of primary healthcare services in the rural communities of Ethiopia is very low. The Ethiopian government has introduced community-based health insurance (CBHI) to improve the health service utilization of the rural community. Thus, this study was conducted to examine the association between CBHI enrollment and child health service utilization in northwest Ethiopia.Patients and Methods: A cross-sectional case comparison study among CBHI enrolled and unenrolled households was conducted. A total of 226 sick children from 2008 surveyed households were included in the study. Bivariate-probit regression analysis was employed to account the endogenous nature of insurance enrollment and child health services utilization.Results: The results showed that the overall sick child healthcare visit in the CBHI enrolled group was about 0.44 (44%) point more compared to those unenrolled households. CBHI enrolled households in the poorest wealth group have a higher probability of visiting healthcare facilities for their sick children (coefficient: 0.13, SD: 0.07, 95% CI: − 0.01, 0.27), whereas CBHI enrolled households with older age household head have a lower probability of visiting healthcare facilities for their sick children (coefficient: − 0.16, SD: 0.08, 95% CI: − 0.32, 0.01).Conclusion: A promising positive effect on sick children’s health services utilization among CBHI enrolled was noticed. Moreover, households in the poorest wealth status and older age head affect the use of sick children’s healthcare services among those CBHI enrolled. Therefore, policy measures to expand benefit packages and supply-side interventions are essential to enhance the effects of CBHI on different health service utilization.Keywords: health insurance, child health services utilization, bivariate-probit regression, northwest Ethiopia